The Group-Leader Self-Assessment (GLSA) Tool: Preliminary Study of Reliability and Validity. Issue 4 (1st October 2020) - Barnes, Mary Alicia; Schwartzberg, Sharan L.; Bedell, Gary; Counselman, Eleanor; Marfeo, Elizabeth
ABSTRACT: Group leadership is a complex process of understanding group dynamics and leader actions. Practitioners of all disciplines need training to effectively lead groups. Psychometrically sound measures are needed to assess effectiveness of group-leader training. The Group Leader Self-Assessment (GLSA) tool, developed to address this need, demonstrates sound psychometric properties including sensitivity to change (pre- to posttest summary scores t = 15.79. p < .0001. Cohen's d = 1.74), strong internal consistency (Cronbach α > .90), and high test retest reliability (ICC (3, 1) =.92; F 26.08; df 1 = 16; p < .0001). Study results suggest GLSA use may help trainees identify goals for skill development and realize growth in leadership abilities.